Anxiety, Depression, and Perceived Social Support in Patients with Transfusion Dependent Beta Thalassemia Major - Asim, Sumbul; Naqvi, Shagufta; Soomro, Maria Ali; Karmani, Veena Kumari; Mehmood, Mehreen; Sharif, Misbah; Bukhari, Syeda Zainab Sultan; Wahid, Iram; Khatian, Anum; Talat, Nisha; Ali, Syed Sanowar; Harani, Mahadev (Journal of Liaquat University of Medical & Health Sciences, 2023)
Objective: To assess the frequency and severity of depression and anxiety, social support and demographic characteristics that could be associated with their disease. Methodology: This cross-sectional study with TD-BTM patients was conducted from four different thalassemia centres (Kashif Iqbal, HELP, Saylani, and Omair Sana Foundation) located in Karachi from December 2018 to May 2019, 197 young (8-18 years) males and 203 (50.8%) young females requiring at least one unit of packed red cells in a month were included with the convenient sampling technique. Psychometrically standardized tests were used. Results: Eleven percent patients suffered severe depression, and a majority (44.2%) had high anxiety. Male patients, patients with comorbid conditions, and patients not satisfied with their treatment had significantly more significant depression; and male patients, patients with no schooling and patients not satisfied with their treatment had significantly greater anxiety. Patients who were schooled belonged to lower socioeconomic status and were not satisfied with their treatment had significantly more significant support from family. Patients who were schooled and had no comorbid conditions were significantly supported by friends. Finally, patients with comorbid conditions were significantly supported by others. Conclusion: In the TD-BTM patients we sampled, most suffered from anxiety and less so with depression. Most patients had strong family support, followed by friends and others. Assessment of depression, anxiety and social support are discussed in the context of psychotherapeutic interventions, which could attenuate full-blown mental disorders in these patients.